An Aggregation-Based Architecture for Unifying Enterprise IT Operations: A Case Study of a Centralized Monitoring System in a Global Industrial Holding - Dmytro Rumiantsev (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
Global industrial corporations often contend with fragmented IT monitoring environments, where disparate tools manage distinct infrastructure domains. This decentralization fosters operational inefficiencies, such as protracted incident diagnostics, redundant alert escalations, and increased resource consumption for root-cause analysis. This paper documents a case study on the design, implementation, and operational impact of a centralized monitoring system at Metinvest Holding, a multinational industrial enterprise. The core objective was to consolidate heterogeneous monitoring platforms into a cohesive, single-pane-of-glass interface to improve operational visibility, streamline diagnostics, and provide high-level strategic oversight for executive management. The research employed a single-case study methodology, coupled with an iterative development process informed by Agile principles. An aggregation and visualization layer was architected using Grafana to integrate data from incumbent systems—including Microsoft SCOM, PRTG Network Monitor, Azure Monitoring, and APC Enterprise Manager—without necessitating their replacement. The two-year development cycle involved continuous collaboration with service engineers. The centralized system yielded substantial improvements in operational efficiency. The number of engineers required for initial, cross-domain incident triage was reduced from an average of three to one. Root-cause identification was significantly accelerated through a holistic, correlated view of infrastructure health, which concurrently minimized alert fatigue and redundant inter-departmental escalations. A novel visualization layer was also developed to furnish executive leadership with an intuitive overview of global IT operational status. This case demonstrates that a non-disruptive, aggregation-based strategy can effectively address the challenges of monitoring fragmentation in large-scale enterprise settings. The findings highlight the value of integrating technical consolidation with user-centric visualization to achieve both operational efficiency and strategic alignment. The architectural principles delineated are broadly applicable to other multinational organizations facing similar IT infrastructure management complexities.